Students' Mathematical Reflective Thinking Ability with Guided Discovery Learning on Pythagorean Theorem Material - Rosa, Kysa Windia; Nurhanurawati, Nurhanurawati; Suryadinata, Nurain (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to determine the effect of the guided discovery learning model on students' mathematical reflective thinking ability. The population in this study were all 8th grade students in one of the schools in Lampung in the 2024/2025 academic year as many as 287 students distributed into 9 classes. The sample in this study took two classes totaling 29 and 27 students respectively which were selected using a cluster random sampling technique. The design used was posttest only control group design. The data collection technique used was a test technique with an instrument in the form of a 4-item mathematical reflective thinking ability test question sheet. Based on the results of the normality test and homogeneity test, it was found that the posttest data from the two groups were normally distributed and homogeneous. Furthermore, the hypothesis test using the independent sample t-test test showed that the mathematical reflective thinking ability of students who followed the guided discovery learning model was higher than the mathematical reflective thinking ability of students who followed the direct instruction model. Therefore, it can be concluded that the guided discovery learning model affects students' mathematical reflective thinking ability.